Pengembangan Pembukuan Sederhana Bank Sampah sebagai Modal Usaha UMKM Gunung Anyar, Surabaya - Hemawan, Muhammad Azzam Firdaus; Soebiantoro, Ugy (Abimanyu : Jornal of Community Engagement, 2024)
Surabaya in 2020 produced 2,091.39 tons of waste per day, based on the assumption of waste generated by each person (Dinas Kebersihan dan Ruang Terbuka Hijau, 2020). One of the solutions in waste management in Surabaya City is to promote waste banks. Likewise, RW 01 Gunung Anyar Village experiences problems in waste management. Not only that, the residents of RW 01 Gunung Anyar Village have an icon of butterfly pea flowers, which is an opportunity to form a sustainable and competitive small business, namely Sari Bunga Telang. However, the business is faced with capital costs for business development in its management. This research bridges the gap between the sustainable waste management approach and the empowerment of Sari Bunga Telang. With a better and organized financial system in the form of a bank pass book and income recapitulation in google spreadsheet, it increases the outcome and efficiency in waste bank processing. Not only that, the income also adds to the business capital of Sari Bunga Telang as a contribution to improving the prosperity of RW 01 residents.